The politics of modern Europe the state and political authority in the major democracies - Keating, Michael (E. Elgar, 1999)
This textbook offers an introduction to politics in Western Europe, based upon the years 1979 to 1999. Mostly geared towards the undergraduate reader, it adopts an empirical approach.